Comparison of electrical energy and power of PV with different cells materials in clear sky day condition. (2022) - Tripathi, Rohit; Tiwari, G.N.; Bhatti, T.S.; Shukla, Manoj K.
Abstract: In present study, a comparison has been made on the basis of gain of the electrical energy and power from solar cells or photovoltaic module. To evaluate the electrical energy and power, five different materials or cases have been considered, which are named as: case (i): c-Si, case (ii): p-Si, case (iii): a-Si, case (iv): CdTe and case (v): CIGS. Each PV module has been considered for the analysis which dimension is 0.605×1 m 2 . For case (i): PV cells are made of silicon crystalline, which is having 0.5 Volts and 4 Amp and 36 cells are connected in series, which are producing 72 W. Such analysis has been studied for a clear sky day condition, New Delhi, India. The comparative study is attempted to choose best for generating electrical energy and power when high electrical enrgy demands in our society. It is also observed that the maximum electrical energy and power have been found for case (i), whereas minimum for case (iii), due to high PV cell temperature. The electrical energy and power have been 1.8 times higher in case (i), than case (iii).